Poly(vinylidene fluoride-trifluoroethylene)/NAY zeolite hybrid membranes as a drug release platform applied to ibuprofen release - Salazar, H. (2015)
Poly(vinylidene fluoride-trifluoroethylene)/NaY zeolite composite membranes were prepared by solvent casting and evaluated as a suitable drug release platform through the evaluation of loading and release of ibuprofen. The membranes were characterized at the morphological, structural and mechanical levels. The 1H-NMR spectra indicate that only the membranes with 16 and 32 % of NaY were useful for IBU encapsulation and the drug release was followed by UV-Vis spectroscopy. The release profile is independent of the zeolite content and can be described by the Korsmeyer-Peppas model. The membrane with 32 % zeolite content releases more than double IBU amount when compared with the membrane with 16 % showing that zeolite content allows tailoring membrane drug release content for specific applications. The drug release platform developed in this work is suitable for other drugs and applications.